Development and evaluation of a restaurant virtual reality training system for enhancing awareness and priority-setting skills - Mai Otsuki; Takashi Okuma (Scientific Reports)
Abstract Characterizing trainees’ cognitive and decision-making processes presents a challenge for trainers, hindering effective on-the-job training (OJT) in the restaurant industry. Thus, objectively evaluating training effectiveness proves to be difficult. To support aspects that are difficult to address through the current OJT, we developed a job-training system based on virtual reality (VR). The system includes both a training mode and a scoring mode. In training mode, trainees wore a head-mounted display (HMD) and held the controller in both hands to perform operations in a virtual restaurant. In scoring mode, instructors could view replays of the trainees’ operations on a PC screen and provide comments. This system targets two elements that pose challenges in real-world scenarios: awareness and priority-setting. Given the importance of evaluating the training effectiveness and user usability of the training system, we designed and conducted an evaluation experiment with 50 novices and 20 experts. Although scores before and after training exhibited no significant differences in the tests using videos recorded in actual settings, both novices and experts highly praised the system’s utility.